Retaliatory killing and human perceptions of Madagascar’s largest carnivore and livestock predator, the fosa (Cryptoprocta ferox) - Merson, SD; Dollar, LJ; Johnson, PJ; Macdonald, DW (Public Library of Science, 2019)
Fosas (Cryptoprocta ferox) are Madagascar’s largest carnivores, occupying much of the island’s forested landscape. This study provides the first evaluation of fosas’ conflict with humans, a problem for many small and medium sized carnivores worldwide. We examined fosas’ predation of poultry, and the subsequent retaliatory killing. Over 1750 households were interviewed across four regions, encompassing Madagascar’s major forest types (deciduous/rainforest) and protected area classifications (national park, reserve and unprotected forest). Predation by fosa was the third highest reported cause (15%) of poultry mortality, with little evidence that coops were effective in reducing predation. Predation of poultry was more prevalent in deciduous forests, and most common during the evenings of the dry season. Over half of all interviewees said they disliked fosas, with loss of poultry the most commonly stated reason. Respondents’ that had suffered poultry depredation and those with lower educational attainment were more likely to dislike fosas. Interviewees that disliked fosas and those that were wealthier were most likely to report having killed a fosa. A minimum of thirty fosas was killed in retaliation by our respondents during the year before the interviews. Given that the fosa population is in decline, and most of Madagascar’s forests are likely to be too small to support sustainable populations, these killings may be detrimental to vulnerable sub-populations. These results shed insight into the cultural perceptions and predation patterns of a medium sized carnivore, with relevance to worldwide human-wildlife conflict of often overlooked smaller carnivores. We suggest that educational programs, guard dogs, poultry disease vaccinations and robust coop construction may be effective for improving attitudes and reducing retaliatory killing.